FEASIBILITY OF A HOME-BASED VIDEO MONITORING TO ASSESS BEHAVIORAL SYMPTOMS AMONG PERSONS WITH DEMENTIA. (11th November 2018) - Samus, Q; Scerpella, Daniel L; Waligora, Kyra; Marx, Katherine; Mahfouz, Sanaa; Plaat, Kaitlin; Roth, David; Gitlin, Laura
Abstract: Development and evaluation of nonpharmacologic interventions for neuropsychiatric symptoms (NPS) in dementia is critically needed but has been significantly limited methodologically by reliance on proxy rated behavioral measures. We conducted a pilot study (n=10) to evaluate feasibility and acceptability of a video monitoring system to capture video and audio behavioral data of persons with dementia and their family caregivers living in the home setting over a 1 week period. This presentation will described the methods of the pilot and will discuss feasibility and participant acceptability of the system. We will also present quantitative summary data on the type and frequency of agitation and other behavioral symptoms, their correlation with "gold standard" proxy rated measures over the same timeframe and consider overall learnings from this pilot including human subjects and privacy protections considerations, technical challenges, and data analytic considerations.